2016
DOI: 10.1108/arj-03-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IFRS adoption on financial reporting quality

Abstract: Purpose: The purpose of this paper is to investigate whether IFRS-based data improve bankruptcy prediction over Australian GAAP-based data. In doing so, we focus on intangibles because conservative accounting rules for intangibles under IFRS required managers to write off substantial amounts of intangibles previously capitalized and revalued upwards under Australian GAAP (AGAAP). Our focus on intangibles is also motivated by empirical evidence that financially distressed firms are more likely to voluntarily ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
23
0
3
Order By: Relevance
“…For instance, Bodle et al . () find that International Financial Reporting Standards (IFRS) rules for intangibles can better predict corporate bankruptcies in Australia.…”
Section: Measurement Of Distress Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bodle et al . () find that International Financial Reporting Standards (IFRS) rules for intangibles can better predict corporate bankruptcies in Australia.…”
Section: Measurement Of Distress Riskmentioning
confidence: 99%
“…Accounting standards‐specific distress risk studies include that of Bodle et al . (), who find that switching from Australian GAAP to IFRS improves the quality of information for predicting bankruptcy, in particular, the accounting treatment of intangible assets. Finally, Ting et al .…”
Section: Determinants Of Financial Distressmentioning
confidence: 99%
“…Skogsvik and Skogsvik (2013) indicate that 70% of early studies on bankruptcy use this design (Zmijewski 1984). An example of more recent bankruptcy research with matched pairs is the study by Bodle et al (2016). and SMOTE (synthetic minority oversampling technique); and for undersampling, RU (random undersampling), UBOCFNN (undersampling based on clustering from the nearest neighbor), and UBOCFMGD (undersampling based on clustering from a Gaussian mixture distribution).…”
Section: Sampling Bias Weighting Resamplingmentioning
confidence: 99%
“…USA: Djatej, Zhou, Gorton, andMcGonigle, 2012;Joos and Leung, 2013; Hong Kong: Helen and Kh, 2013; Ghana: Mensah, 2013;Abedana, Omane-Antwi, and Oppong, 2016; Turkey: Chebaane and Othman, 2013;Balsari and Varan, 2014;Kılıça, Uyar and Ataman, 2014;Vietnam: Phan, Mascitelli, and Barut, 2014. Libya: Zakari, 2014; Bangladesh: Hossain et al, 2015a;Hossain, Hasan,and Safiuddin, 2015b; Australia: Bodle, Cybinski, & Monem, 2016). These studies are briefly reviewed in the following section.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%
“…They also found that there are a lot of technical Challenges faced by the users while adopting IFRSs such as lot of conflicts with local GAAP. Bodle et al (2016) examined the impact of IFRS adoption on financial reporting quality by assisting in predicting bankruptcy. They found that restrictive accounting rules for intangibles under IFRS improve the quality of financial statement data by enabling better bankruptcy prediction.…”
Section: Related Literature and Previous Studiesmentioning
confidence: 99%